2015
DOI: 10.1038/ncomms8949
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant copy number variations detected in cerebral palsy

Abstract: Cerebral palsy (CP) represents a group of non-progressive clinically heterogeneous disorders that are characterized by motor impairment and early age of onset, frequently accompanied by co-morbidities. The cause of CP has historically been attributed to environmental stressors resulting in brain damage. While genetic risk factors are also implicated, guidelines for diagnostic assessment of CP do not recommend for routine genetic testing. Given numerous reports of aetiologic copy number variations (CNVs) in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
116
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 60 publications
2
116
2
2
Order By: Relevance
“…No significant pathogenic CNVs were identified with aCGH in this study, unlike other previous reports,3, 36 in which pathogenic CNVs were identified in 9.6–31% of patients with aCGH. This wide range of proportions could be explained by variations in case selection or differences in the criteria used to evaluate pathogenicity.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…No significant pathogenic CNVs were identified with aCGH in this study, unlike other previous reports,3, 36 in which pathogenic CNVs were identified in 9.6–31% of patients with aCGH. This wide range of proportions could be explained by variations in case selection or differences in the criteria used to evaluate pathogenicity.…”
Section: Discussioncontrasting
confidence: 96%
“…Both genetic and environmental factors contribute to the etiology of CP. Recent studies have suggested that a larger number of rare pathogenic genetic variants2 or pathogenic copy number variations (CNVs)3 contribute to CP than previously expected 4. This suggests that “masquerading” genetic diseases can be misdiagnosed as CP 5.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the candidate gene or variant has not yet been identified (3). Secondly, it has been shown that MA can enlight account for 10-20% of CPs (3,4). Chromosomal MA is a new, high-resolution chromosome analysis technique.…”
mentioning
confidence: 99%
“…Beneath neonatal asphyxia, there may be neuromuscular diseases such as Prader-Willi syndrome, congenital myotonic dystrophy, and many clinical conditions leading to hypotonia (1). Possible genetic factors should be investigated in patients with a history of premature birth or hypoxia who present with motor problems prior to the diagnosis of CP (1,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation